The mitochondrial function of peripheral blood mononuclear cells in frail older patients - Huang, Tingting; Qin, Li; Zhang, Danmei; Tong, Qiangwei; Zhu, Qianqian; Ding, Guoxian; Liu, Juan (Experimental gerontology, 2024)
Frailty increases the incidence of geriatric syndromes and even the risk of death in old adults. However, the diagnostic criteria for frailty are inconsistent because of complex pathological processes and diverse clinical manifestations. To determine the effective biomarker and recognize frail status early, we investigated the correlation of mitochondrial morphology and function of human peripheral blood mononuclear cells (PBMCs) with frailty status in older adults. This Cross-sectional study followed 393 participants (aged 25–100 years, female 31.04 %) from the First Affiliated Hospital of Nanjing Medical University. The frailty status of subjects was assessed by the physical frailty phenotype (PFP) scale. We analyzed mitochondria functions including mitochondria copy number (mtDNAcn), the mRNA expressions of mitochondrial dynamics-related genes mitofusin 1(MFN1), mitofusin 2(MFN2), optic atrophy protein-1(OPA1), fission protein-1(FIS1) and dynamin-related protein 1(DRP1), mitochondrial oxidative respiration and reactive oxygen species(ROS) levels in PBMCs. Mitochondria morphology, size, and number were observed by transmission electron microscopy (TEM). After adjustment for sex and BMI, mtDNAcn, the mRNA expression of FIS1, mitochondrial respiratory function (proton leak, maximum oxygen consumption, and respiratory reserve) and ROS level were significantly correlated with age (P = 0.031, 0.030, 0.042, 0.003, 0.002, 0.022, respectively). After correcting for age, sex, and BMI, mtDNAcn and the mRNA expression of OPA1 were correlated with 4 m gait speed respectively (P = 0.003, 0.028, respectively). Compared with non-frail people, mtDNAcn, the mRNA expression of MFN1, mitochondrial basal respiration, proton leak, maximum oxygen consumption, ATP production and space capacity were significantly decreased in frail older adults (P = 0.013, 0.036, 0.026, 0.024, 0.012, 0.032, 0.020, respectively). ROS levels were significantly increased in the frail group (P = 0.016). Compared with non-frail people, the number, length, and perimeter, area of mitochondria were reduced in frail group under TEM (all P < 0.001). Mitochondrial dysfunctions (decreased mtDNAcn, impaired mitochondrial morphology, imbalanced mitochondrial dynamic, impaired mitochondrial respiratory function, and increased ROS levels) were significantly correlated with frail status. •Mitochondrial morphology and function were significantly correlated with age.•Mitochondrial function is closely related to frailty parameters.•Frail patients have impaired mitochondrial morphology and function.•Mitochondrial DNA copy number is a sensitive indicator to assess frailty.